Comparing High, Moderate And Low Performance Exporters: Evidence From Malaysia - Mohamad, Osman; N. Wheeler, Colin (Asian Academy of Management (AAM), 1996)
The industrialisation strategy which aimed at diversifying the Malaysian economic base saw the rising importance of the manufacturing sector in terms of employment and export earnings. Exporting shifted from being an option to a strategic imperative for firms in the manufacturing sector when the Industrial Master Plan (1985) was launched. The current national policy is to export to non-traditional markets. While competing on cost competitiveness is continued to be emphasised, the exporting firms are also encouraged to upgrade their marketing skills. This paper reports the findings of a study on Malaysian firms' export marketing behaviour and performance.